A Price Discrimination Theory of Coupons - Narasimhan, Chakravarthi (Marketing Science, 1984)
The objective of this paper is to analyze the consumer's decision in electing to use cents-off coupons distributed by manufacturers of consumer products. Arguing that the decision to use coupons is based on the tradeoff between costs of using coupons and the savings obtained, it is shown that coupons can serve as a price discrimination device to provide a lower price to a particular segment of consumers. Based on a price theoretic model, it is shown that the users of coupons are more price elastic than nonusers of coupons and that the opportunity cost of time and other household resource variables are determinant factors in consumers' decisions. Implications derived from the model are tested using diary panel data.